Alternative Health Care among Type 2 Diabetes in ASEAN Countries: A Scoping Review - Parliani, Parliani; Pearkao, Chatkhane (Jurnal Pendidikan Keperawatan Indonesia, 2024)
Introduction: The prevalent rate of diabetes is increasing among the world and ASEAN countries itself. The treatment using alternative health care (AHC) is one of exist medication among diabetes patients. In addition, the evidence on the management of diabetes through the use of traditional medicine has not been addressed before. Objective:  The purpose of this scoping review was to review and summarize the AHC therapies in literature that are the most well-known and successful for glycemic control complication and the burden among diabetes patients in ASEAN countries. Methods: To access all studies and articles related to the scoping review’s aim, seven databases were searched. The seven data based included PubMed, ProQuest, ScienceDirect, SCOPUS, Google Scholar, the Cochrane Library, and CINAHL unlimited until August 12, 2023. The search method used keywords “diabetes”, “alternative health care”, “ASEAN” and “Indonesia”, modifying the search statements of these phrases so that they were compatible with the various databases. Results: The result of study after critical appraisal using JBI critical appraisal checklist for RCT were found three kinds of alternative health care for diabetes patients, first herbs or traditional medication which are herbal extract of cinnamon bark powder 3%, pandan leaf 6%, and bay leaf 9% and herbs extract of breadfruit life, second community care, there is CIIC (Community Integrated Intermediary Care), and third, mind and body therapies such as acupuncture, acupressure and message. Conclusion: The utilization of AHC (Alternative Health Care) has demonstrated its efficacy in the management of diabetes, leading to enhanced clinical outcomes and a decrease in both blood glucose levels and associated burdens. Despite the scarcity of empirical data, it is widely acknowledged that the recommended therapeutic interventions yield advantages in inducing relaxation, which subsequently contributes to the alleviation of stress.